A novel molecular test for influenza B virus detection and lineage differentiation. Issue 12 (24th April 2014) - Wong, Chloe K.S.; Tsang, Gary C.H.; Chan, Kwok‐Hung; Li, Olive T.W.; Peiris, Malik; Poon, Leo L.M.
<x xml:space="preserve">Abstract</x> Contemporary influenza B viruses are classified into two groups known as Yamagata and Victoria lineages. The co‐circulation of two viral lineages in recent years urges for a robust and simple diagnostic test for detecting influenza B viruses and for lineage differentiation. In this study, a SYBR green‐based asymmetric PCR assay has been developed for influenza B virus detection. Apart from identifying influenza B virus, the assay contains sequence‐specific probes for lineage differentiation. This allows identifying influenza B virus and detecting influenza B viral lineage in a single reaction. The test has been evaluated by a panel of respiratory specimens. Of 108 influenza B virus‐positive specimens, 105 (97%) were positive in this assay. None of the negative control respiratory specimens were positive in the test (N = 60). Viral lineages of all samples that are positive in the assay (N = 105) can also be classified correctly. These results suggest that this assay has a potential for routine influenza B virus surveillance. J. Med. Virol. 86:2171–2176, 2014. © 2014 Wiley Periodicals, Inc.